Pelaksanaan Konsep Kecerdasan Jamak Pada learning centers Di PAUD Dellia Creative School Kota Bengkulu - Dewi Yuliana Safitri; Parlan Parlan; Agus Rahmat (Jurnal Pendidikan Sepanjang Hayat, 2020)
This study aims to describe: (1)the Implementation of multiple intelligences concept in learning center at education for early age Dellia creative school and; (2) Supporting factors and the inhibiting implementation of multiple intelligences concept at learning center in education for early age Dellia creative school. The Implementation concept of multiple intelligences in the learning center defined as a process of applying innovative methods of learning in early childhood using centers based on the plural intelligence of children in early age. This research is descriptive research with qualitative approach. The subjects of this study were the managers/principals and also the educators of dellia education for early age creative school. The data were collected using observation method, interview, and documentation. The Researcher are the main instruments in conducting this research assisted by observation guides, interview guides, and documentation guidelines. The Techniques used in data analysis are data reduction, data display, and taking the conclusion. The Triangulation done to explain the validity of the data using source of triangulation.The results of the research indicate that: 1) the Implementation consept of multiple intelligences at learning center in education for early age Dellia creative school is done in three stages: (a) planning includes making RKH (daily lesson plan)  and RKM (weekly lesson plan), but the planning itself is not written in RKH (daily lesson plan), the kinds of multiple intelligence development; (B) the implementation includes four footholds: first is footholds of the main environmental, second is the pre-game experience, third is the current playing ground and the last is foothold of the after-play experience. The Plural intelligence developement can be identified from the type of offered play by the educator; (C) the assessment is performed by observation, checklists, anecdotes and assignments packed in middle of semester and the ends of semester reports. 2) the supporting factors of the implementation center approched based on multiple intelligence is: (a) the instruments and the materials are adjusted to the level of child development achievement; (B)a good cooperation between the educators, employees and parents of education for early age Dellia creative schools, while the inhibiting factors are: (a) the changing of learners mood; (b) the lack of teaching personnel.Keywords: multiple intelegences, center, learning